Joint iterative decision feedback channel estimation and detection for Turbo coded V-BLAST MIMO-OFDM systems - QIAO Xiao-qiang1; CAI Yue-ming1; XU Xin1; XU You-yun1 (Tongxin xuebao)
For Turbo coded V-BLAST MIMO-OFDM systems,a joint iterative decision feedback channel estimation and detection scheme were presented,which combined the Turbo iterative decoding with least square channel estimation,and made full use of the soft systematic bits and soft parity bits of Turbo iterative decoding to improve the channel estimation performance.The simulation results showed that not only the error propagation was corrected at low signal-noise-ratio but also the channel estimation performance of the whole system was improved greatly.Furthermore,the scheme is applicable for very bad channel environments.